Multiple Pulmonary Metastases following Total Removal of a Bilateral Parasagittal Meningioma with Complete Occlusion of the Superior Sagittal Sinus: Report of a Case. (15th July 2012) - Nakano, Masataka; Tanaka, Toshihide; Nakamura, Aya; Watanabe, Mitsuyoshi; Kato, Naoki; Arai, Takao; Hasegawa, Yuzuru; Akiba, Tadashi; Marushima, Hideki; Kanetsuna, Yukiko; Abe, Toshiaki
Abstract : Pulmonary metastases of benign meningiomas are extremely rare. The case of a 34-year-old man with bilateral parasagittal meningioma who developed pulmonary metastases is described. The meningioma was an enormous hypervascular tumor with invasion of the superior sagittal sinus. The tumor was resected completely and histologically diagnosed as transitional meningioma. The Ki-67 labeling index was 5%. Four months after operation, the patient subsequently developed bilateral multiple lung lesions later identified as metastases. The lung lesions were partially removed surgically and histologically diagnosed as meningothelial meningioma WHO grade I. The Ki-67 labeling index was 2%. The histological findings demonstrated that the tumor occupied the arterial lumen and the perivascular space, suggesting that pulmonary tumors might metastasize via the vascular route. The histopathological features and mechanisms of metastasizing meningiomas are reviewed and discussed.